The Steady-State Internal Redox State (NADH/NAD) Reflects the External Redox State and Is Correlated with Catabolic Adaptation in Escherichia coli - de Graef, Mark R. (American Society for Microbiology, 1999)
Escherichia coli MC4100 was grown in anaerobic glucose-limited chemostat cultures, either in the presence of an electron acceptor (fumarate, nitrate, or oxygen) or fully fermentatively. The steady-state NADH/NAD ratio depended on the nature of the electron acceptor. Anaerobically, the ratio was highest, and it decreased progressively with increasing midpoint potential of the electron acceptor. Similarly, decreasing the dissolved oxygen tension resulted in an increased NADH/NAD ratio. As pyruvate catabolism is a major switch point between fermentative and respiratory behavior, the fluxes through the different pyruvate-consuming enzymes were calculated. Although pyruvate formate lyase (PFL) is inactivated by oxygen, it was inferred that the in vivo activity of the enzyme occurred at low dissolved oxygen tensions (DOT ≤ 1%). A simultaneous flux from pyruvate through both PFL and the pyruvate dehydrogenase complex (PDHc) was observed. In anaerobic cultures with fumarate or nitrate as an electron acceptor, a significant flux through the PDHc was calculated on the basis of the redox balance, the measured products, and the known biochemistry. This result calls into question the common assumption that the complex cannot be active under these conditions. In vitro activity measurements of PDHc showed that the cellular content of the enzyme varied with the internal redox state and revealed an activity for dissolved oxygen tension of below 1%. Whereas Western blots showed that the E3 subunit of PDHc (dihydrolipoamide dehydrogenase) did not vary to a large extent under the conditions tested, the E2 subunit (dihydrolipoamide acetyltransferase) amount followed the trend that was found for the in vitro PDHc activity. From this it is concluded that regulation of the PDHc is exerted at the E1/E2 operon (aceEF). We propose that the external redox state (measured as the midpoint potentials of those terminal acceptors with which the cell has sufficient capacity to react) is reflected by the internal redox state. The latter may subsequently govern both the expression and the activity of the two pyruvate-catabolizing enzymes.